Descriptive modeling for methane emission from three major livestock in Sarawak - Kiat P.E.; Malek M.A.; Shamsuddin S.M. (International Center for Scientific Research and Studies, 2023)
Rising concerns of methane emission, especially from natural enteric fermentation process of livestock, has caused the implementation of 2006 Intergovernmental Panel on Climate Change (IPCC) Guidelines Tier 1 methodology, which is the simplest method in quantifying greenhouse gases emissions, for quantification of methane emission from three major livestock in Sarawak. Lack of specific country-specific emission factor has led to prediction of future emission. Fitness functions are the inputs used in coding for producing forecasted emission, and can be obtained from the Statistical Package for the Social Sciences (SPSS) software. SPSS is then employed to access the correlation between amount of livestock and methane emission generated. Linear regression model is applied in SPSS software which generates three important tables namely Model Summary Table, Analysis of Variance (ANOVA) Table and Coefficients Table for result analysis. Fitness functions produced from the Coefficients table generated by SPSS illustrated strong correlation between livestock quantity and methane emitted. 2014-2018. IJASCA.